Penerapan Hukuman Pada Jarimah Menjual Dan Menyimpan Minuman Keras (Khamar) Dalam Perspektif Qanun Jinayat (Studi Di Mahkamah Syariah Lhokseumawe) - desky, teku ananta; Zurnetti, Aria (Delicti : Jurnal Hukum Pidana Dan Kriminologi, 2024)
Sentencing disparities are not confined to general courts but are also evident within the Mahkamah Syar’iyah. Notable inconsistencies can be seen in several cases adjudicated by the Mahkamah Syar’iyah Lhokseumawe. In Case No. 10/JN/2018/MS.Lsm, the defendant was sentenced to 20 lashes; in Case No. 9/JN/2018/MS.Lsm, to 25 lashes; and in Case No. 1/JN/2020/MS.Lsm, to a fine of 25 grams of pure gold. All cases were prosecuted under Article 16(1) of Aceh Qanun No. 6 of 2014 on Jinayat Law. This article investigates judicial approaches to sentencing in cases involving jarimah (criminal acts) related to the sale and storage of alcoholic beverages (Khamar) in the Mahkamah Syar’iyah Lhokseumawe. Employing an empirical juridical method, the study draws on document analysis and interviews, using a descriptive-analytical framework. Both primary and secondary data are used to depict the legal reality and are subsequently analysed with reference to statutory regulations and legal theories. The findings indicate that disparities in sentencing arise due to the Qanun’s provision of only maximum penalties, granting judges broad discretion in determining sentences. Factors such as the defendant’s background influence judicial reasoning and may lead to divergence in punishment. These differences often generate debate within judicial panels prior to verdicts. Therefore, judges must ensure objectivity by thoroughly considering all evidentiary elements including witness testimonies, documents, and physical evidence, based on facts established during the trial